Kinetika Pengeringan Lapisan Tipis Daun Jati Belanda (Thin Layer Drying Kinetics of Guazuma Ulmifolia Leaves) - Hendri Syah; Armansyah Halomoan Tambunan; Edy Hartulistiyoso; Lamhot Parulian Manalu (Jurnal Keteknikan Pertanian, 2020)
The objectives of this study were to determine a suitable thin layer drying model to describe the drying kinetics of Guazuma ulmifolia leaves and determine the mass transfer parameters of Guazuma ulmifolia leaves. The drying of Guazuma ulmifolia leaves was conducted in a laboratory scale dryer with various temperature (40oC, 50oC, and 60oC) and relative humidity (30%, 40%, 50% and 60%). Five drying models, namely, Newton, Henderson and Pabis, Page, Midilli-Kucuk, and Verma et al. were fitted to the drying data. The drying curve of guazuma leaves did not show a constant drying period during the drying period. The models suitability were compared base on coefficient of determination (R2), root square mean errors (RSME), and reduced mean square of deviation (X2). It was found that, among the models evaluated, the Midilli and Kucuk model is the best to describe the drying kinetics of Guazuma ulmifolia leaves. The effective moisture diffusivity was found to be in the range of 10-13 – 10-12 m2/s and the convective mass transfer coefficient was in the range of 10-9 – 10-10 m/s. The activation energy value was found to be 89.21 kJ/mol.